Molecular modeling and simulation of pH effects in lipid bilayers - Viçosa, Diogo Ruivo dos Santos Vila, 1987- (2016)
Tese de doutoramento, Bioquímica (Bioquímica Teórica), Universidade de Lisboa, Faculdade de Ciências, 2015